A biological evaluation of DNA damage detected by comet assay in healthy populations residing in areas that differ in lung cancer incidence - Worapa Heepchantree (2018)
The comet assay was performed to evaluate the effect of environmental exposure between human populations residing in two areas that differ in lung cancer incidence, Saraphi ( n = 91) and Chom Thong ( n = 94). Three parameters, the tail length, tail intensity, and tail moment, were used to detect DNA damage in peripheral blood and stimulated lymphocytes with and without the DNA repair inhibitor, aphidicolin. Internal standards, cryopreserved isolated lymphocytes, and isolated lymphocytes irradiated with 2 Gy gamma rays, were used to correct the interexperimental variability. Results revealed a significant difference between two populations only when the tail length was used to measure DNA damage. The evaluation of various potential confounding factors, such as gender, pesticide exposure, smoking, alcohol drinking, and fermented tea leaf or betel nut chewing, indicated no significant influence in DNA damage. In conclusion, significant difference in DNA damage, detected only by tail length between the two populations residing in the areas with different incidence of lung cancer, may reflect a nonhazardous level of exposure to toxic substances. Copyright© Taylor & Francis Group, LLC.